1999
DOI: 10.1038/sj.leu.2401487
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immunological dissection of diffuse large B cell lymphoma: CD5+, and CD5− with CD10+ groups may constitute clinically relevant subtypes

Abstract: Diffuse large B cell lymphoma (DLBL) constitutes the greatest percentage of adult non-Hodgkin's lymphomas and represents a diverse spectrum of lymphoid neoplasms. Clinicopathologic, phenotypic and genotypic findings were correlated and compared for 63 DLBL cases to investigate whether they represent clinically relevant subtypes. They were all cyclin D1 negative and were phenotypically divided into three groups, ie group I (CD5 + type, n = 11), group II (CD5 − CD10 + type, n = 19), and group III (CD5 − CD10 − t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
102
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 11 publications
(20 reference statements)
8
102
2
1
Order By: Relevance
“…Multiple studies have looked at the expression of bcl-2 using immunostains and most have found no difference in overall survival. 16,23,[27][28][29][30][31][32][33][34][35] However, some studies have found that bcl-2 expression is associated with a significantly worse overall survival, 3,[36][37][38][39][40][41][42] or event-free survival. [29][30][31]36,37 The discrepancies related to bcl-2 expression and prognosis may be related to the underlying subgroups of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have looked at the expression of bcl-2 using immunostains and most have found no difference in overall survival. 16,23,[27][28][29][30][31][32][33][34][35] However, some studies have found that bcl-2 expression is associated with a significantly worse overall survival, 3,[36][37][38][39][40][41][42] or event-free survival. [29][30][31]36,37 The discrepancies related to bcl-2 expression and prognosis may be related to the underlying subgroups of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of T-cell antigen expression in B-cell non-Hodgkin's lymphomas remains somewhat controversial. CD5 expression in some series of extranodal marginal zone lymphoma 27,28 and de novo diffuse large B-cell lymphoma 22,23,29 has been associated with a clinically aggressive course and tendency for dissemination, although other studies have failed to support these findings. 30 Only one of five patients with clinical follow-up data in our study died of disease.…”
Section: Diffuse Blastoid B-cell Lymphomamentioning
confidence: 97%
“…[18][19][20] Although CD5 expression is characteristic of chronic lymphocytic leukemia/small lymphocytic lymphoma and mantle cell lymphoma, it is rarely observed in other categories of B-cell non-Hodgkin's lymphoma. [21][22][23] CD43 expression, although relatively common in several subtypes of B-cell non-Hodgkin's lymphoma, is unusual in follicular lymphoma (3%). 24 However, CD43 expression is detected relatively often in cases of high-grade follicular lymphoma both with and without diffuse areas.…”
Section: Diffuse Blastoid B-cell Lymphomamentioning
confidence: 99%
“…Similarly, Uherova et al (7) reported that CD10 expression in DLBCL correlated with shortened overall survival. In contrast, Harada et al (18) found no difference in overall survival between CD10(ϩ) and CD10(Ϫ) DLBCL patients. The availability of paraffin-reactive antibodies directed against CD10 suggests that retrospective studies with fixed tissue may be possible to confirm the prognostic significance of CD10 on DLBCL.…”
Section: Discussionmentioning
confidence: 87%
“…CD10 is expressed in a subset of DLBCL, a heterogeneous group of non-Hodgkin's lymphomas (6,7,17,18). The majority of DLBCL patients can be cured with current treatment regimens, whereas a minority fail to achieve complete remission and rapidly progress to death.…”
Section: Discussionmentioning
confidence: 99%